From 2,772 segments to five personas: Summarizing a diverse online audience by generating culturally adapted personas - Joni Salminen; Sercan Şengün; Haewoon Kwak; Bernard J. Jansen; Jisun An; Soon-gyo Jung; Sarah Vieweg; D. Fox Harrell (First Monday, 2022)
Understanding users in the era of social media is challenging, requiring organizations to adopt novel computation-aided approaches. To exemplify such an approach, we retrieved information on millions of interactions with YouTube video content from a major Middle Eastern media outlet, to automatically generate personas that capture how different audience segments interact with thousands of individual content pieces. Then, we used qualitative data to provide additional insights into the automatically generated persona profiles. Our findings provide insights into social media usage in the Middle East and demonstrate the application of a novel methodology that generates culturally adapted personas of social media audiences, summarizing complex social analytics data into human portrayals that are easy to understand by end users in real organizations.